Physiotherapists' experiences of the management of anterior cruciate ligament injuries. (May 2016) - von Aesch, Arlene V.; Perry, Meredith; Sole, Gisela
Abstract: Background: While extensive research has been reported for management of anterior cruciate ligament (ACL) injuries, variation in treatment by physiotherapists is evident. Objectives: To explore physiotherapists' experiences regarding ACL injury rehabilitation and factors that influenced physiotherapists' decision making for ACL rehabilitation, and to elicit what research physiotherapists perceived would support their management of these patients. Design: Qualitative study. Methods: Fifteen physiotherapists from six private clinics in New Zealand participated in semi-structured interviews. The interviews were recorded, transcribed verbatim and the general inductive approach was used to develop key themes. Results: Participant's management strengths were evident by their intent and commitment to provide expert rehabilitation, using a biopsychosocial approach and evidence-informed practice. The lengthy management process (including prolonged rehabilitation and referral processes) and interprofessional disconnect concerned participants. Translational research was needed for clear directions for exercise prescription and milestones for return to sports and occupation following ACL injury. Conclusions: Participants provided a biopsychosocial and evidence-based approach to ACL injury management. Potential areas of improvement include simplifying the referral process and enhancing communication between physiotherapists and other health professionals. Future research should focus on clarifying areas of ACL rehabilitation uncertainty, or collating results in an accessible and usable format for clinical practice. Highlights: 15 Physiotherapists were interviewed regarding experiences with ACL rehabilitation. A biopsychosocial and research-informed approach to management was described. The prolonged rehabilitation and referral processes concerned the participants. Interprofessional disconnect was also discussed by some participants. Research with clear directions for exercise prescription and return to sports and occupation should be considered.